Unpicking British Values. (2nd December 2021) - Marycz, Adam
Abstract : In November's magazine, myself and Julia Gouldsboro explored whether we should 'reform' or 'reclaim' British Values. This month, in part one of my reflection on British Values, I explore in more depth what they really mean and how they are currently implemented in practice.